2011
DOI: 10.1371/journal.pone.0018021
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Exposure to 50 Hz Magnetic Fields Modifies Menadione-Induced Genotoxic Effects in Human SH-SY5Y Neuroblastoma Cells

Abstract: BackgroundExtremely low frequency (ELF) magnetic fields (MF) are generated by power lines and various electric appliances. They have been classified as possibly carcinogenic by the International Agency for Research on Cancer, but a mechanistic explanation for carcinogenic effects is lacking. A previous study in our laboratory showed that pre-exposure to ELF MF altered cancer-relevant cellular responses (cell cycle arrest, apoptosis) to menadione-induced DNA damage, but it did not include endpoints measuring ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 22 publications
5
44
0
Order By: Relevance
“…We have previously shown that exposure to ELF MFs (50 Hz, 100-300 mT) alter cellular responses to DNA damage induced by menadione (MQ), resulting in decreased integrity of the genome [13,14]. A more recent study also indicated that similar exposure may induce genomic instability (persistently elevated frequency of genetic changes in the progeny of exposed cells), which is highly relevant for possible carcinogenic effects [15].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that exposure to ELF MFs (50 Hz, 100-300 mT) alter cellular responses to DNA damage induced by menadione (MQ), resulting in decreased integrity of the genome [13,14]. A more recent study also indicated that similar exposure may induce genomic instability (persistently elevated frequency of genetic changes in the progeny of exposed cells), which is highly relevant for possible carcinogenic effects [15].…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify and characterize the cellular processes involved in the potential proliferative effects of ELF MF, a number of studies have investigated the in vitro response to those fields when administered in combination with different chemical species including antioxidants like melatonin or tamoxifen (14)(15)(16)(17)(18)(19), or radical-inducing agents like menadione (20) and tumor promoters like DMBA (21).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the experimental data produced in relation to the potential genotoxicity of ELF-MF exposure are reminiscent of that produced by epidemiological studies in that it is moderately conflicting. This point was typified by the intra-laboratory inconsistencies published by Luukkonen et al (2011) and Luukkonen et al (2014) who in contrast to their earlier study (Luukkonen et al, 2011), more recently illustrated that ELF-MF exposure (100 µT, 24 hours) was able to induce micronuclei in human SH-SY5Y neuroblastoma cells at 8 and 15 days postexposure (Luukkonen et al, 2014).…”
Section: Experimental Studiesmentioning
confidence: 90%
“…Despite this, the majority of studies conducted to date have found no consistent evidence of magnetic field induced effects on genotoxicity using an array of field intensities: 0.001-1 mT (Paile et al, 1995;Luceri et al, 2005;Stronati et al, 2004;Testa et al, 2004;Luukkonen et al, 2011;Saha et al, 2014), and 5-400 mT (Antonopoulos et al, 1995;Tateno et al, 1998;Miyakoshi et al, 2000). Yet there have also been several studies, both in vivo and in vitro where positive correlations have been reported; for example a significant three-fold elevation in SCE was observed in mouse m5S cells exposed to 400 mT (50 Hz) for 40 hours (Yaguchi et al, 1999).…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation